A reforma do conselho de segurança da onu e as pretensões do Brasil - Berquó, André Taddei Alves Pereira Pinto (2011)
This work has by object to examine the thematic of the Security Council s reform and the pretensions of Brazil, to contribute in a comprehension of a subject so interesting, relevant and urgent to the International Society and the United Nations. The Organ in question is responsible for the monitoring of international peace and security, being the principal organ of the United Nations, monopolizing the capacity of adopting coercive measures of the Organization, which are the sanctions and the use of the Force, to any Estate-Member that disrespects the principles and purposes of the UN s Charter. However, this Organ, very important for that the UN can manage and stabilize the International Society, needs reforms in its structure, that preserves an obsolete composition of fifteen members, being five permanents with right of veto, beyond the regulamentation and the amplification of its attributions, so that the UN can develop conjoined with its members each purpose and principle included in its Constituent Treaty. The UN s Security Council reform is also a subject very defended by Brazil, although it doesn t have a foreign policy well defined allowing to have a major international force than it actually has and that prejudices the country in its pretensions, which aren t very well defined too. It is the State-member of UN that for ten times occupied the elective seats of the organ, beside of Japan, that is the one that more occupied the function of elective member of Security Council. Its activism during its biennials always was for promoting the pacific ways of controversies instead of taking more rigid measures, which are the sanctions and the authorized force of the Security Council to prevail its purposes, pleading a seat as permanent member and the amplification of the number of permanent and elective members to equilibrate the forces inside the organ. The research will be developed in three parts: to explore the generality of the International Society and of the United Nations to insert the UN s Security Council; to develop and to discuss the UN s Security Council reform; and to debate the interests that the Brazil has about this Organ.